Gourd, Luffa—Luffa cylindrica (L.) Roem., Luffa aegyptica Mill., and Luffa acutangula (L.) Roxb. - James M. Stephens (EDIS)
This document provides an overview of luffa gourds, specifically Luffa cylindrica, Luffa aegyptica, and Luffa acutangula, commonly known as vegetable sponges or loofahs. It describes their botanical characteristics, cultivation requirements in warm climates like Florida, and dual-purpose use as both edible vegetables and natural cleaning sponges. The article outlines differences between angled and smooth varieties, pollination habits, and harvesting techniques. It also includes guidance on preparing mature fruits for sponge use, emphasizing their novelty and limited commercial cultivation in the region. Original publication date May 1994.